Mecanismos linguístico-discursivos e diferenciação de linguagem e género - Guedes, Alexandra; casim (Mulheres no Discurso - Women in Discourse, 2025)
Gender identity is intrinsic to linguistic expression and is constructed through discourse, the linguistic-discursive mechanisms used, and the communicative attitude adopted. Certain linguistic choices are associated by society with a particular gender, which contributes to the construction of gender stereotypes, particularly in the area of language. Due to the perpetuation of stereotypical categorizations, this study aims to investigate the gender differentiation in discourse, in order to identify and characterize regularities in the linguistic uses between men and women. To this end, a questionnaire was designed, in which utterances potentially representative of male and female speech were tested, organized by types of speech acts and characterized by different degrees of illocutionary force. The answers provided by the participants met initial expectations and demonstrate that, indeed, there are linguistic uses that are identified as being typical of men and women. It is mainly concluded, based on the qualitative and quantitative analysis of the data, that expressive and commissive acts with high illocutionary force and directive acts with mitigated illocutionary force were more frequently associated with women and, contrary to what was expected, assertive acts with intensified illocutionary force were not predominantly associated with men.